Need Funding? Tips on Where to Find and How to Apply for Grants. (2nd September 2016) - Brett, Christine E. W.
Abstract : There are many organizations that provide grants (both monetary and in the form of equipment) to help promote healthy lifestyles. This article shares a few tips on how to find grants and write grant proposals.